Designing Electronic Measuring Instruments by PC Microcomputer - Amaral Pereira, Wilton Ney; Martins Rezende, Ulysses; Carneiro Adami, Antonio Rodolpho; Azevedo, José Antonio (Revista Ciências Exatas, 2009)
This paper deals with a partnership example between two professional scholars with two productive field specialists to conceiving and settlement an exclusive profile and innovative enterprise. In this partnership is outstanding the high synergic potential of this kind of initiative, not many turned to account in Brazil, where, regardless occasional exceptions, the academic and the productive society segments accomplish its tasks with reduced interaction. To actuate in the high-tech subjects, where the high scientific qualification human resources are essential, the productive field usually fall back on finished solutions, concerning themselves only with manufacturing process and choosing rather the foreign intellectual property. Otherwise, the academic world deals with knowledge research normally displaced with our industrial reality, local material resources or marketing demands. This paper explains the alliance of the four electronic engineers, half in college teaching and half in action on the industrial and trading field, bringing financial resources and professional skills together to make an exclusively national enterprise. Key-words: enterprising, electronic, manufacturing, measurement, instrument.